(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the psychological factors of the formation of social perceptions of young people about the digital space. In the context of digital technologies, the interaction of a person with the information environment, social identification, communicative activity and changes in cognitive processes are scientifically substantiated. Also, the influence of factors that shape social perceptions in the process of adapting young people to the digital environment - family, educational institutions, media and social networks - is studied. Based on the results of the study, recommendations are developed for the development of the digital culture of young people.